Exploration of Philosophy in Traditional Silat Kumango West Sumatra - Febby Syafita Putri; Ardi Nusri; Albadi Sinulingga; Nurhayati Simatupang (UNIB Press, 2023)
The point of this examination is to figure out the philosophy contained in the customary Kumango silat in West Sumatra region. The examining procedure utilized purposive testing method or with specific contemplations so there were 7 sources utilized in this examination. Information assortment methods in this examination utilized perception procedures, documentation studies and meetings with old Kumango Conventional Silat educators. The information obtained will be depicted in subjective expressive structure so an itemized and thorough picture can be obtained. The consequences of the exploration uncover that in Kumango Customary Silat there are numerous methods of reasoning, one of which is the colloquialism